1995
DOI: 10.1520/jfs13786j
|View full text |Cite
|
Sign up to set email alerts
|

Forensic DNA Testing on Skeletal Remains from Mass Graves: A Pilot Project in Guatemala

Abstract: A reliable method for extracting DNA from teeth was developed and successfully applied to a set of 12 skeletons recovered from two 10-year-old Guatemalan mass graves. Attempts to identify the remains by mitochondrial DNA (mtDNA) testing were hampered by low sequence diversity. Our findings demonstrate the feasibility of using DNA typing to identify victims from mass graves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(60 citation statements)
references
References 23 publications
3
56
0
1
Order By: Relevance
“…The maternal lineage affinity between the Chibchan and Maya groups was based on one contemporary Maya group from Guatemala (Boles et al 1995;Melton et al 2007Melton et al , 2013. However, this association has now been confirmed in this study analyzing the sequences of pre-Hispanic Mexican Maya and sequences from the Caribbean Islands, Colombia, and contemporary Maya groups from Mexico and Guatemala, as well as Central and South American Chibchan speakers from previous reports (Table 3).…”
Section: Network Analysis Of Haplogroup Asupporting
confidence: 81%
See 1 more Smart Citation
“…The maternal lineage affinity between the Chibchan and Maya groups was based on one contemporary Maya group from Guatemala (Boles et al 1995;Melton et al 2007Melton et al , 2013. However, this association has now been confirmed in this study analyzing the sequences of pre-Hispanic Mexican Maya and sequences from the Caribbean Islands, Colombia, and contemporary Maya groups from Mexico and Guatemala, as well as Central and South American Chibchan speakers from previous reports (Table 3).…”
Section: Network Analysis Of Haplogroup Asupporting
confidence: 81%
“…haplogroup B than haplogroup A (González-Martín et al 2015), and the ancient bones collected in a Quiché Indian village, located close to the provincial capital of Santa Cruz de Quiché, revealed the presence of 16 different mtDNA haplotypes, among which haplogroup B has the highest frequency (Boles et al 1995). The pre-Hispanic Maya population of this study displayed a high frequency of haplogroup A (60.53%), followed by haplogroup C (34.21%), a very low frequency of haplogroup D (5.26%), and the complete absence of haplogroup B.…”
Section: Mitochondrial Haplogroup Frequenciesmentioning
confidence: 99%
“… Sequence analysis of human mtDNA (mitochondrial DNA) has been demonstrated to be a valid and reliable tool for the genetic characterization of forensic biological specimens [1][2][3]. The human mtDNA is a 16569 np (nucleotide pair) closed, circular molecule located within the cytoplasmic mitochondria.…”
Section: Introductionmentioning
confidence: 99%
“…The SNPs that occur in the mitochondrial genome are very important tool in the species identification, forensic studies as well as anthropological and evolutionary research (Boles et al, 1995). Harumi et al (2004) observed the single nucleotide polymorphism in the D-loop region in chicken mitochondrial DNA and reported 11 SNPs.…”
Section: Introductionmentioning
confidence: 99%